APPLICATION OF THE GUIDED INQUIRY LEARNING MODEL TO IMPROVE STUDENTS LEARNING OUTCOMES ON ECOLOGICAL MATERIALS AT SMAN 1 MUTIARA, PIDIE REGENCY - Moh Affifuzzin; Andi Ulfa Tenri Pada; Wiwit Artika; Muhibbuddin Muhibbuddin; Samingan Samingan (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
ABSTRAKTujuan dilaksanakan penelitian untuk mengetahui perbedaan peningkatan hasil belajar peserta didik antara kelas eksperimen dengan kelas kontrol pada materi ekologi di SMAN 1 Mutiara. Metode yang dipilih quasi experimental denngan teknik purposive sampling, terdiri dari dua kelas X. Hasil uji independent sample t-test memperlihatkan thitung yang didapatkan 3,2 lebih besar dari ttabel pada taraf sig. 5% yaitu 1,67 maka ada perbedaan peningkatan hasil belajar peserta didik antara kelas eksperimen dengan kelas kontrol di SMAN 1 Mutiara.Kata kunci: Inkuiri Terbimbing, Hasil Belajar, Ekologi.ABSTRACTThe purpose of the research was to determine the difference in the improvement of student learning outcomes between the experimental class and the control class on ecological material at SMAN 1 Mutiara. The method chosen was quasi-experimental with purposive sampling technique, consisting of two class X. The results of the independent sample t-test showed that the tcount obtained was 3.2 greater than ttable at the sig level. 5% which is 1.67 then there is a difference in the increase in student learning outcomes between the experimental class and the control class at SMAN 1 Mutiara.Keywords: Guided Inquiry, Learning Outcomes, Ecology.